GIS-Based Analysis of a Rainwater Harvesting System in the Multipurpose Hall of Quaid-e-Awam University of Engineering, Science, and Technology - Kumar, V.; Mukwana, K. C.; Jatoi, A. R.; Hassan, M.; Jakhrani, A. Q.; Siyal, A. A.; Zaman, K. U.; Kumar, L. (Engineering, Technology & Applied Science Research, 2022)
Drinking water availability has become a major issue. Rainwater Harvesting Systems (RHSs) amass and store rainwater for future use. In Pakistan, drinking water availability has become a major issue. Rainwater can be used as a constant alternative to clean water resources. Google Earth Pro (GEP) is utilized in this paper to select suitable locations for the installation of RHSs. The decision must not be too excessive, must fit in buildings that have small available space, and must cover the needs of bigger buildings. The required capacity for an RHS to cope with an unusually high water shortage in the study area was calculated using GEP and ArcGIS. The total estimated amount of rainwater harvesting potential during the average annual monsoon period from 2012 to 2021 is 1064.056 m3 from the 13452.05 m2 available area from rooftops and plain surfaces. The capacity of storage containers is primarily based on day-to-day spills and breadth.